HISTONE DEACETYLASE 7 INHIBITION IN A MURINE MODEL OF GRAM-NEGATIVE PNEUMONIA-INDUCED ACUTE LUNG INJURY - Kasotakis, George (Shock, 2020)
BACKGROUND: Pulmonary infections remain the most common cause of Acute Respiratory Distress Syndrome (ARDS), a pulmonary inflammatory disease with high mortality, for which no targeted therapy currently exists. We have previously demonstrated an ameliorated syndrome with early, broad spectrum Histone Deacetylase (HDAC) inhibition in a murine model of gram-negative pneumonia-induced Acute Lung Injury (ALI), the underlying pulmonary pathologic phenotype leading to ARDS. With the current project we aim to determine if selective inhibition of a specific HDAC leads to a similar pro-survival phenotype, potentially pointing to a future therapeutic target. METHODS: C57Bl/6 mice underwent endotracheal instillation of 30×10(6) Escherichia coli (strain 19138) vs saline (n=24). Half the infected mice were administered Trichostatin A (TSA) 30 minutes later. All animals were sacrificed 6h later for tissue sampling and HDAC quantification, while another set of animals (n=24) was followed to determine survival. Experiments were repeated with selective siRNA inhibition of the HDAC demonstrating the greatest inhibition vs. scrambled siRNA (n=24). RESULTS: TSA significantly ameliorated the inflammatory phenotype and improved survival in infected-ALI mice, and HDAC7 was the HDAC with the greatest transcription and protein translation suppression. Similar results were obtained with selective HDAC7 siRNA inhibition compared to scrambled siRNA. CONCLUSION: HDAC7 appears to play a key role in the inflammatory response that leads to ALI after gram-negative pneumonia in mice.